2004
DOI: 10.1079/wps20035
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional factors affecting excreta/litter moisture and quality

Abstract: The control of excretanitter moisture and quality is a priority in the modern poultry industry, to avoid environmental and animal welfare problems and to reduce productivity losses. Control implies the reduction of their amounts and moisture content. Several factors can affect them, some related to management and housing, others related to diseases and finally, dietary factors. The paper reviews some nutritional aspects that could interfere with the moisture and quality of poultry excretaflitter, focusing on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…In the modern poultry industry, controlling excreta moisture and quality to avoid environmental and animal welfare problems is very important (Francesch & Brufau, 2004). Some studies showed that the excreta moisture, the amount of caked litter and consequently production of ammonia may increase when stocking density increases (Dozier et al, 2005;Sorensen, Su, & Kestin, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the modern poultry industry, controlling excreta moisture and quality to avoid environmental and animal welfare problems is very important (Francesch & Brufau, 2004). Some studies showed that the excreta moisture, the amount of caked litter and consequently production of ammonia may increase when stocking density increases (Dozier et al, 2005;Sorensen, Su, & Kestin, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the excreta moisture, the amount of caked litter and consequently production of ammonia may increase when stocking density increases (Dozier et al, 2005;Sorensen, Su, & Kestin, 2000). Wet litter promotes proliferation of pathogenic bacteria (Francesch & Brufau, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…FPD is often caused by a high litter moisture content associated with nutritional factors (Francesch and Brufau, 2004;Eichner et al, 2007;Mayne et al, 2007;Cengiz et al, 2012). Soyabean meal-based diets have relatively high α-galactoside concentration (above 2%), which increases the risk of FPD in turkeys .…”
Section: Effect Of Dietary Na On Excreta Moisture and Fpd Incidencementioning
confidence: 99%
“…It is an important risk factor for excess litter moisture and leg problems, common in intensively farmed chickens and turkeys (Francesch andBrufau, 2004: Venäläin-en et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Barley and wheat contain variable amounts of non-starch polysaccharides (NSP) which increase digesta viscosity and reduce nutrient absorption and performance in broilers (Edney et al, 1989;Wang et al, 2005;García et al, 2008) and laying hens (Lázaro et al, 2003;Mirzaie et al, 2012). In layers, a high NSP content of the diet is associated with an increase in dirty eggs (Francesch and Brufau, 2004).…”
Section: Introductionmentioning
confidence: 99%